Unveiling promising targets in gastric cancer therapy: A comprehensive review - Wenke Li; Jing Wei; Mo Cheng; Ming Liu (Molecular Therapy: Oncology)
Gastric cancer (GC) poses a significant global health challenge, ranking fifth in incidence and third in mortality among all malignancies worldwide. Its insidious onset, aggressive growth, proclivity for metastasis, and limited treatment options have contributed to its high fatality rate. Traditional approaches for GC treatment primarily involve surgery and chemotherapy. However, there is growing interest in targeted therapies and immunotherapies. This comprehensive review highlights recent advancements in GC targeted therapy and immunotherapy. It delves into the mechanisms of various strategies, underscoring their potential in GC treatment. Additionally, the review evaluates the efficacy and safety of relevant clinical trials. Despite the benefits observed in numerous advanced GC patients with targeted therapies and immunotherapies, challenges persist. We discuss pertinent strategies to overcome these challenges, thereby providing a solid foundation for enhancing the clinical effectiveness of targeted therapies and immunotherapies.